A new species of Leptolalax (Anura: Megophryidae) from Gunung Mulu National Park, Sarawak, East Malaysia (Borneo) - Dehling, J. Maximilian; Matsui, Masafumi (Zootaxa, 2013)
We describe a new species of Leptolalax from Gunung Mulu National Park in eastern Sarawak, Malaysian Borneo. The new species had been assigned to Leptolalax dringi and Leptolalax gracilis in the past. It is shown to differ from both these species and from all other species of the genus by a unique combination of morphological characters including large body size, rounded snout, interorbital distance being smaller than width of upper eyelid, bipartite subgular vocal sac in males, basal toe webbing, shagreened skin with tiny tubercles on dorsum and dorsal side of head, angled supratympanic fold, small pectoral glands, absence of supraaxillary glands and ventrolateral glandular ridges, spotted venter, advertisement call consisting of long series of 8–289 notes, each composed of three or four pulses, and dominant frequency at 7225– 9190 Hz, with prominent frequency modulation.